Thoracoscopic repair of iatrogenic bronchial injury in a neonate during bronchogenic cyst excision - Revathy Menon; Kirtikumar J Rathod; Darshana Rathod; Prawin Kumar; Taruna Yadav; Arvind Sinha (Wolters Kluwer Medknow Publications, 2023)
Thoracoscopic surgery was not previously accepted in the neonatal population due to inappropriate instrumentation and lack of experience. However, our experience in the last few decades has slowly yet steadily established its safety and efficacy. The major advantages that thoracoscopy offers are early recovery and fewer long-term complications. However, we are aware that this comes at the cost of a steep learning curve and the potential challenge of facing certain complications which may compel a conversion to open. There is a paucity of literature regarding intraoperative complications of neonatal thoracoscopy and its management. Conversion to open thoracotomy is appropriate, keeping patient safety in mind, and any decision made to continue management of a complication thoracoscopically is technically demanding. Iatrogenic bronchial injury is one such rare complication of thoracoscopy with a limited mention in literature. We describe below a 25-day-old patient with a bronchogenic cyst who sustained injury to the left bronchus during thoracoscopic cyst excision, which was successfully repaired thoracoscopically.